EDUKASI PENCEGAHAN DAN PENGOBATAN DIARE ANAK MENGGUNAKAN EXPERIENTAL METHODS PADA IBU-IBU PKK DI DESA PASAR KEMIS KABUPATEN BANJAR - Muhammad Ikhwan Rizki; Herningtyas N. Lingga; Valentina Meta Srikartika; Difa Intannia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Diarrhea is a condition in which there is an increase in the frequency of bowel movements, and a decrease in the consistency (mass) of feces. Pasar Kemis Village is located in Banjar Regency, South Kalimantan Province, which still uses latrines on the banks of the river to defecate. Experiential methods are training methods that prioritize flexible and dynamic communication using visual aids or videos that can be used as educational methods. The purpose of the activity is to increase the knowledge of PKK mothers in the prevention and treatment of diarrhea in children. Community service activities began with the socialization of activities to the Village Head and PKK mothers, pretests on knowledge related to diarrhea in children, delivery of material using experiential methods, question and answer discussions, and evaluation of activities using questionnaires. The results of the implementation of community service in Pasar Kemis Village, Kertak Hanyar District, Banjar Regency using experiential methods showed that there was an increase in the knowledge of PKK mothers about the prevention and treatment of diarrhea in children from 55.43% to 86.62%..